Innovation in training Family Mediators in England and Wales - Amel Ketani (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
The purpose and goal of this paper is to consider how it is possible to improve the current mediation training in England and Wales. A significant recommendation made in this paper concerns the duration and method of delivery of the family mediation training. The current training only lasts two weeks and does not give sufficient time for family mediators to perhaps fully absorb the key skills and understandings surrounding their work. Therefore the suggestion made in this paper is that the training should last one year and should be awarded upon successful completion of all classroom and online course requirements (blended learning approach to teaching). This paper also considers whether the program electives should allow trainees to concentrate on specific modules and expand their learning in a wide range of areas related to working with families in conflict. It is recommended that each module should assess trainees either through a Multiple Choice Test (MCT), a viva, a role play, a coursework or a written assessment.
Keywords: A29; 330; Education; Learning; Teaching; Innovation; Assessments; Portfolio; Mediators and Law